KETIMPANGAN PRODUKSI ANGKUTAN BARANG DAN PENUMPANG TIAP MODA TRANSPORTASI JALUR UTAMA PANTURA JAWA - Agus Taufik Mulyono (Jurnal HPJI (Himpunan Pengembangan Jalan Indonesia), 2016)
Abstract Java Island plays an important role in maintaining the smooth and accelerated distribution of freight and passengers to support the improvement of the national economy. An important issue on transportation across the island of Java in three decades is a very significant disparities heaping load of freight and passengers between the traffic lanes the north coast of Java and central and southern lanes. The government needs to implement the share mode target in order to achieve reduction in the logistics travel time from 2.75 hours/100 km (2015) to 1.0 hours/100 km (2019) for balancing the northern and southern regions. There are some actions needed including: (1) the acceleration of the construction of the Trans Java toll road, (2) the widening and improvement of the national road geometric in central and southern regions, (3) the widening and improvement of road geometric and the addition of cross-connecting lines, (4) the revitalization of rail track width of 1,067 mm to 1,450 mm along with rail facilities capable of carrying larger and more secure loads, (5) the development of infrastructure networks and integrated services; and (6) increasing awareness of local government together with the police in controlling the right of way of national roads from local socio-economic activities. Keywords: transport production, mode share, travel time, intermodal  Abstrak Pulau Jawa memegang peranan penting dalam mempertahankan kelancaran dan percepatan distribusi angkutan barang dan penumpang untuk mendukung peningkatan ekonomi nasional. Persoalan penting pada lintas transportasi Pulau Jawa dalam 3 dasawarsa adalah terjadinya kesenjangan yang amat signifikan penumpukan beban angkutan barang dan penumpang antara jalur lintas Pantai Utara Jawa dan lintas tengah maupun lintas selatan. Pemerintah perlu merealisasikan target mode share agar tercapai penurunan waktu tempuh angkutan barang dari 2,75 jam/100 km (2015) menjadi 1,0 jam/100 km (2019) untuk mewujudkan keseimbangan wilayah utara dan selatan. Oleh karenanya perlu dilakukan: (1) percepatan pembangunan jalan tol Trans Jawa; (2) pelebaran dan perbaikan geometrik jalan nasional lintas tengah dan lintas selatan; (3) pelebaran dan perbaikan geometrik jalan serta penambahan jalur penghubung lintas; (4) revitalisasi jalan rel dari lebar 1.067 mm menjadi 1.450 mm beserta sarana kereta api yang mampu mengangkut beban barang yang lebih besar dan aman; (5) pembangunan jaringan prasarana dan pelayanan terpadu; dan (6) peningkatan kepedulian Pemerintah Daerah beserta polisi dalam mengendalikan gangguan fungsi jalan nasional dari kegiatan sosial ekonomi lokal pada ruang manfaat jalan nasional. Kata-kata kunci: produksi angkutan, mode share, waktu tempuh, antarmoda